Infrared thermography as a method for monitoring and preventing injuries in soccer - Noya, J.; Sillero, M.; Gomez, P. M.; Pastrano, R. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Infrared thermography is considered as a valid and non-invasive diagnostic method [1] of different pathologies [2], including some musculo-skeletal problems as the lumbar pain [3]. Modern equipments make possible very accurate and objective recording of the body surface with a single picture. Recently, thermography has been purposed as a method not only for diagnosing but also for monitoring rehabilitation processes [4]. Methods: We recorded the body temperature of 23 professional players of the C.D. Toledo S.A.D. (Age= 24,9; SD= ± 3,5) on 24 days of its 2-months precompetitive period. Two thermographic pictures for each player (frontal and dorsal, of the trunk and lower limbs) were taken with a ThermaCAM TM SC640 (FLIR SYSTEMS, Portland) before starting the training season. Mean temperature of the muscular groups: abdominal (AB), quadriceps (Q,R&L), adductors (AB,R&L), anterior leg (AL,R&L), lumbar (L), hamstrings (H,R&L) and calves (C,R&L) and the joints: anterior knees (AK,R&L), posterior knees (PK,R&L), and ankles (A,R&L) were calculated from the pictures by the software `ThermaCAM Reporter`. Additionally, the level of nuisance of those areas was assessed every day by the player from 1 (no pain) to 10 (injured). Temperatures were compared with the declared level of nuisance considering three groups (1 = No pain; 2 - 3 = Low pain; > 4 = High pain). Areas affected by physiotherapeutic treatments were excluded from the sample. Rough reports and pictures from each player were daily reported to the physiotherapist of the team. Results: ANOVA results point out a direct relationship between the declared level of nuisance of the area and its temperature both in ankles (F[AR] = 9.20; p < 0.05 and F[AL] = 3.99; p < 0.05) and knees (F[PKR] = 5.34; p < 0.05 and F[PKL] = 9.14; p < 0.05). There were also found significant differences for temperatures (aprox. 0.5 degrees) between the painful and non-painful limb on the knee (F[AK] = 14.36; p < 0.05) and hamstrings (F[H] = 3.9; p < 0.05) results. None serious injury has been produced among the players during the 2-months of the study. Discussion: We concluded that infrared thermography is a valid, fast and convenient method of preventing soccer injuries. We suggest that this technique could also be applied to monitor and diagnose injuries and to quantify training loads in sports